2021
DOI: 10.3389/fcell.2020.615461
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Mitochondrial Impairment in Parkinson's Disease: Challenges and Opportunities

Abstract: The underlying pathophysiology of Parkinson's disease is complex, but mitochondrial dysfunction has an established and prominent role. This is supported by an already large and rapidly growing body of evidence showing that the role of mitochondrial (dys)function is central and multifaceted. However, there are clear gaps in knowledge, including the dilemma of explaining why inherited mitochondriopathies do not usually present with parkinsonian symptoms. Many aspects of mitochondrial function are potential thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 199 publications
(201 reference statements)
0
76
0
1
Order By: Relevance
“…In contrast, as a generic term, "mitochondrial dysfunction" oversimplifies the multifaceted nature of mitochondrial biology in health and disease. PD-associated mitochondrial dysfunction presents with a variety of molecular events, including impaired mitochondrial biogenesis, increased release of reactive oxygen species (ROS), defective mitophagy and trafficking, electron transport chains (ETC) dysfunction, variations in mitochondrial dynamics, calcium (Ca2+) imbalance, neuroinflammation, and possible indirect influences on mitochondrial homeostasis from presumably unrelated pathways (e.g., alpha-synuclein deposition) [8]. The centrality of mitochondria in cellular functioning and the convergence of mammalian metabolism on mitochondria suggest that potential therapies must address a complex web of interconnected pathways [9].…”
Section: Mitochondrial Dysfunction In Idiopathic and Monogenic Parkinson's Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, as a generic term, "mitochondrial dysfunction" oversimplifies the multifaceted nature of mitochondrial biology in health and disease. PD-associated mitochondrial dysfunction presents with a variety of molecular events, including impaired mitochondrial biogenesis, increased release of reactive oxygen species (ROS), defective mitophagy and trafficking, electron transport chains (ETC) dysfunction, variations in mitochondrial dynamics, calcium (Ca2+) imbalance, neuroinflammation, and possible indirect influences on mitochondrial homeostasis from presumably unrelated pathways (e.g., alpha-synuclein deposition) [8]. The centrality of mitochondria in cellular functioning and the convergence of mammalian metabolism on mitochondria suggest that potential therapies must address a complex web of interconnected pathways [9].…”
Section: Mitochondrial Dysfunction In Idiopathic and Monogenic Parkinson's Diseasementioning
confidence: 99%
“…A promising approach can derive from enhanced insights into the individual disease genetics (e.g., by presymptomatic genetic testing or polygenetic risk scoring) [133]. However, blood-or neuroimaging-based assessments of mitochondrial dysfunction can substantially enhance our current understanding of mitochondrial dysfunction's temporal and spatial dynamics in vivo [8]. Current knowledge gaps of essential aspects of mitochondrial biology need to be closed for the rational design of gene therapies.…”
Section: Special Considerations For Mitochondrial Gene Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…PARK2 and PARK6, which encode for parkin and PINK1 respectively, are genes responsible of the onset of familial Parkinson's disease (PD) a progressive degenerative disorder of the central nervous system characterized by dopaminergic neurodegeneration in the substantia nigra pars compacta. Several studies in PD models proved hallmarked dysfunctions of mitochondria, in particular, defect of the respiratory chain complex I, which plays a central role in mitochondrial oxidative phosphorylation (OXPHOS) efficiency and capacity [1], depletion of ATP production, increased reactive oxygen species (ROS) and oxidative stress, anomalies in mitochondrial dynamics, trafficking and turnover, dysregulation in calcium homeostasis, and protein misfolding and aggregation [2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Also, studies performed in postmortem PD patient brain tissue have shown decreased mitochondrial biomass, bioenergetic capacity, and altered mitochondrial distribution of mitochondria within the cell bodies and neurites ( Schapira et al, 1990 ; Keeney et al, 2006 ; Navarro et al, 2009 ; Mallach et al, 2019 ). Thus, therapies that reverse mitochondrial dysfunction are a promising therapeutic approach; however, various human clinical trials targeting mitochondrial dysfunction in PD have been unsuccessful in reversing the course of disease (e.g., disease progression and motor symptoms) ( Beal et al, 2014 ; Kieburtz et al, 2015 ; Prasuhn et al, 2021 ). Thereby, additional basic science studies that functionally dissect the role of the various mitochondrial localized PD-linked gene products and their function are essential to broaden our understanding of mitochondria and their role in PD pathogenesis, ultimately leading to targeted therapies against PD.…”
Section: Introductionmentioning
confidence: 99%